Faces of Inequality: Gender, Class and Patterns of Inequalities in Different Types of Welfare States - Walter Korpi (Luxembourg Income Study (LIS), 2000)
Research on welfare states and inequality has tended to be bifurcated, focusing either on class or on gender. This paper combines gender and class in an analysis of patterns of inequalities in different types of welfare states in 18 countries. Whereas a major dimension of class inequality can be described in terms of material standards of living, in the advanced Western countries it is fruitful to conceptualize gender inequality in terms of agency. In analyses of gender as well as of class inequalities, welfare states have been seen as significant intervening variables. However, major problems have emerged in attempts to devise typologies of welfare states that are of heuristic value in analyses of gender inequality as well as of class inequality. This paper describes the development of gendered agency inequality during the period after the Second World War in 18 OECD countries in the arenas of democratic politics, tertiary education, and labor force participation. Class inequality is measured in terms of disposable house income based on LIS data. The paper develops a new typology of welfare states based on institutional structures of relevance for gender inequality as well as class inequality. The combination of gender and class throws new light on the driving forces behind inequalities and on the role of welfare states in this context. Gender inequality is conceptualized in terms of agency. The paper presents a new typology of welfare states based on institutional structures of relevance for gender inequality as well as class inequality. The combination of gender and class throws new light on the driving forces behind inequalities and on the role of welfare states in this context.
Keywords: 330; Einkommensverteilung; Geschlecht; Sozialstaat; OECD-Staaten